Promoting a well-dispersion of MoO3 nanoparticles on fibrous silica catalyst via one-pot synthesis for enhanced photoredox environmental pollutants efficiency. (December 2022) - Izzudin, N.M.; Jalil, A.A.; Ali, M.W.; Aziz, F.F.A.; Azami, M.S.; Hassan, N.S.; Fauzi, A.A.; Ibrahim, N.; Saravanan, R.; Hassim, M.H.
Abstract: The coexistence of pharmaceutical compounds and heavy metals in the aquatic environment has resulted in complications in the treatment process and thus, causing uproar among the citizens. The radical-based photocatalysis technology has aroused as an excellent method to eliminate both heavy metal and pharmaceutical compounds in the water. Herein, reported the utilization of the microemulsion technique for the preparation of nanoporous fibrous silica-molybdenum oxide (FSMo) towards simultaneous photocatalytic abatement of hexavalent chromium (Cr(VI)) and tetracycline (TC). The FESEM analysis showed the spherical morphology of the FSMo catalyst with dendrimeric silica fiber. The synthesized FSMo catalyst exhibited narrowed bandgap, high crystallinity, and well Mo element dispersion for enhanced photo-redox of Cr(VI) and TC. Remarkably, simultaneous remediation of the Cr(VI) and TC over FSMo demonstrated superior photocatalytic efficiency, 69% and 75%, respectively, than in the individual system, possibly due to the effective separation of photoinduced charges. The introduction of the Mo element to the silica framework via microemulsion technique demonstrated better dispersion of Mo compared to the incipient wetness impregnation method and thus, yielded higher photocatalytic activity towards simultaneous removal of TC and Cr(VI). Besides, quenching experiments revealed the electrons and holes as the active species that play a dominant role in the simultaneous photo-redox of Cr(VI) and TC. Lastly, the FSMo catalyst demonstrated high stability after four continuous cycles of simultaneous photocatalysis reactions, implying its potential as a suitable material for practical wastewater treatments. Graphical abstract: Image 1 Highlights: Nanoporous of FSMo was efficaciously synthesized via microemulsion method. FSMo catalyst demonstrated a preserved spherical morphology with dendrimeric silica fibre. The well-dispersion of Mo element in the FSMo catalyst greatly inhibits the electron-hole recombination. FSMo showed the 75% and 69% towards simultaneous remediation of Cr(VI) and TC, respectively. h +, .OHads, and e − are noted as the reactive species that play significant role in the photoredox of Cr(VI) and TC.